2020
DOI: 10.3390/ijerph17155467
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Gaseous Ozone Therapy in Conjunction with Periodontal Treatment on Glycated Hemoglobin Level in Subjects with Type 2 Diabetes Mellitus: An Unmasked Randomized Controlled Trial

Abstract: Background: It is established that inflammation is involved in the pathogenesis of Type 2 Diabetes Mellitus (T2DM) by promoting insulin resistance and impaired beta cell function in the pancreas. Among the hypothesized independent risk factors implicated in the pathogenetic basis of disease, periodontal infection has been proposed to promote an amplification of the magnitude of the advanced glycation end product (AGE)-mediated upregulation of cytokine synthesis and secretion. These findings suggest an interrel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 42 publications
4
31
0
4
Order By: Relevance
“…In this study, the mechanisms by which EAEC 042 triggers this inflammatory event were assessed. The immunofluorescent staining analysis of expression of FadA on the FN 12230 USF81 strain, fad-A-complementing clone, confirmed that FadA is equally exposed on the bacterial cell surface, promoting adherence and invasion of host cells [59], [60], [61]. This study provided the first evidence that the expression of FadA was correlated to placental colonization in vivo [60].…”
Section: Pathogenic Mechanism Of Fn: the Role Of Fusobacterium Adhesisupporting
confidence: 57%
See 4 more Smart Citations
“…In this study, the mechanisms by which EAEC 042 triggers this inflammatory event were assessed. The immunofluorescent staining analysis of expression of FadA on the FN 12230 USF81 strain, fad-A-complementing clone, confirmed that FadA is equally exposed on the bacterial cell surface, promoting adherence and invasion of host cells [59], [60], [61]. This study provided the first evidence that the expression of FadA was correlated to placental colonization in vivo [60].…”
Section: Pathogenic Mechanism Of Fn: the Role Of Fusobacterium Adhesisupporting
confidence: 57%
“…The immunofluorescent staining analysis of expression of FadA on the FN 12230 USF81 strain, fad-A-complementing clone, confirmed that FadA is equally exposed on the bacterial cell surface, promoting adherence and invasion of host cells [59], [60], [61]. This study provided the first evidence that the expression of FadA was correlated to placental colonization in vivo [60]. Studies aimed at elucidating the process of FN translocation into host cells, include genetic analysis defining components that are required for FadA activity [32].…”
Section: Pathogenic Mechanism Of Fn: the Role Of Fusobacterium Adhesimentioning
confidence: 81%
See 3 more Smart Citations